Ideologico-worldviewing considerations by Augustine Voloshin - Nyorba, Lyudmyla (Actual Problems of Mind, 2017)
The author describes the life and the work of Augustine Voloshin — a not very renowned Ukrainian politician acting between two world wars in Transcarpathia. The paper highlights theoretical and world-viewing foundations of the national renewal of the transcarpathian Ukrainians elaborated by Voloshin.